Deliverable 2.1 Report on present observing capacities and gaps: ocean and sea ice observing system - Ludwigsen, Carsten Ankjær; Pirazzini, Roberta; Sagen, Hanne; Hamre, Torill; Sandven, Stein; Stette, Morten; Babiker, Mohamed; Schewe, Ingo; Soltwedel, Thomas; Behrendt, Axel; Andersen, Ole B.; Beszczynska-Möller, Agnieszka; et al. (Zenodo, 2018)
A major goal of WP2: “Exploitation of existing observing systems” is to analyze strengths, weaknesses, gaps in spatial/temporal coverage, and missing monitoring parameters of the existing observation networks and databases in relation to the requirements from different user groups. This report is prepared to assess the existing ocean and sea ice observing systems in the Arctic, primary those where the INTAROS partners have responsibilities, but also where the partners contribute to larger, international observing systems. A core activity in the first 18 months of WP2 has been to conduct a survey where partners have responded to three sets of questionnaires: Questionnaire A: Existing Arctic In-situ Observing Systems, Questionnaire B: In-situ data collections, and Questionnaire C: Satellite Products. The survey has covered the scientific disciplines addressed in INTAROS, including atmosphere, ocean and terrestrial disciplines. The focus of the survey has been on in-situ observing systems, which is the priority of INTAROS, while satellite observing systems are treated more generally. This report therefore provides more details on selected in-situ systems and data collections than previous surveys and inventories. The reason or the detailed survey is that INTAROS will develop and demonstrate machine-to-machine operations between data repositories, following the FAIR data management principle (“Findable, Accessible, Interoperable and Re-usable”). An expected outcome of the survey is identification of selected observing systems and data collections that will be used further in the project, especially in WP5 (“Data integration and management”) and WP6 (“Application of iAOS towards stakeholders”). A major part of the report is a status description of in situ observing systems that are operated by the partners (Section 2). In INTAROS we identify a set of data collected from the same types of instruments and platforms over time to be an observing system (for example CTD surveys by ships, network of moorings, glider ...